Tafsir Pluralisme Agama dalam Perdebatan: Studi Pemikiran Tokoh Jaringan Islam Liberal (JIL) dan Institute for The Study of Islamic Thought and Civilization (INSISTS): The Interpretation of Religious Pluralism in Debate: A Study of the Thoughts of Figures from the Liberal Islam Network (JIL) and the Institute for The Study of Islamic Thought and Civilization (INSISTS) - Fathiyaturrahmah Fathiyaturrahmah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2013)
This research examines the interpretation of religious pluralism in the debate between the Liberal Islam Network (JIL) and the Institute for The Study of Islamic Thought and Civilization (INSISTS). The results indicate that JIL constructs its arguments in favor of religious pluralism based on four Quranic arguments, while INSISTS opposes religious pluralism with two Quranic arguments. JIL employs the Ushul Fiqh approach in interpreting pluralism verses, whereas INSISTS uses a contextual approach—both textual and historical. However, the inclusive view of JIL and the exclusive view of INSISTS each have their own implications. Penelitian ini membahas penafsiran pluralisme agama dalam perdebatan antara Jaringan Islam Liberal (JIL) dan Institute for The Study of Islamic Thought and Civilization (INSISTS). Hasil penelitian menunjukkan bahwa JIL membangun argumen mereka untuk mendukung pluralisme agama berdasarkan empat argumen quranik, sementara INSISTS menolak pluralisme agama dengan dua argumen quranik. JIL menggunakan pendekatan Ushul Fiqh dalam menafsirkan ayat-ayat pluralisme, sedangkan INSISTS menggunakan pendekatan kontekstual—baik konteks teks maupun historis. Namun, pandangan inklusif JIL dan eksklusif INSISTS memiliki implikasi masing-masing.